Development of a plant-based vaccine against brucellosis: stable expression of Brucella abortus OMP25 in transgenic tobacco - Qashqai, Mansoure; Bertan, Emrah; Erisen, Semiha; Ozbek, Tulin; Vural-Korkut, Senay (SPRINGER, 2025)
Brucellosis, caused by Brucella species, is a global threat to livestock farming, resulting in economic losses and socio-economic challenges, particularly in rural areas. Despite its impact, no licensed human vaccines are available. Animal vaccination remains the most cost-effective control method, but traditional vaccine production is expensive. Edible vaccines, using plants as bioreactors to produce immunogenic antigens, offer a low-cost alternative by eliminating complex purification processes. This study developed a transgenic plant by expressing the Brucella abortus outer membrane protein OMP25 in tobacco plants. OMP25, a conserved transmembrane protein with high immunogenicity, was cloned into a Gateway pDONR vector via a Boundary Pairing reaction and transferred to a binary destination vector via a Left-Right reaction. The destination vector was introduced into Agrobacterium tumefaciens and subsequently used for Agrobacterium-mediated transformation of tobacco plants. Transgenic plants were selected on media containing kanamycin, and the expression of the transgene was verified through the fluorescence of green fluorescent protein. Microcallus formation and shoot development on selective media confirmed kanamycin resistance and the successful integration of the transgene. After phenotypic selection, genomic DNA was extracted from transgenic plants and analyzed by PCR (Polymerase Chain Reaction) using primers specific to the OMP25 gene. Positive PCR results validated the successful integration of the OMP25 gene into the plant genome. Gene expression was further confirmed at the RNA level through real-time quantitative PCR (qRT-PCR) and at the protein level via Western blot analysis. Future studies will evaluate immune responses in animal models. This approach demonstrates the potential for low-cost, effective vaccines to combat brucellosis, addressing critical economic and public health challenges.
Keywords: Agrobacterium Tumefaciens; Subunit vaccine; Gateway cloning; Transgenic plant; LUMAZINE SYNTHASE; ELICITS; Biochemistry & Molecular Biology; Biotechnology & Applied Microbiology